Sistem Pendukung Keputusan Pemilihan Motor Bekas menggunakan Metode Weighted Product pada PT Sukses Motor - Munajar Munajar; Khusnul Khotimah; Hanasa Shelviani; Imam Himawan; Aminah Aminah (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2026)
This study presents the development of a decision support system to recommend the best used motorcycles for prospective buyers at PT. Sukses Motor. The system aims to provide faster, more accurate, and objective recommendations while improving customer service. The Weighted Product (WP) method was applied to evaluate motorcycle alternatives based on multiple criteria, including price, condition, production year, mileage, and buyer preferences. System development included requirements analysis, UML-based design, implementation using PHP and MySQL, and functional testing. Data were collected through interviews with sales staff and company records. The results show that the system successfully generates recommendation rankings that match buyer needs and preferences. In addition to identifying the most suitable motorcycle, the system provides several alternative recommendations, enabling buyers to compare available options before making a purchasing decision. The proposed system improves the efficiency and objectivity of the recommendation process and can serve as a reference for developing decision support systems in other multi-criteria decision-making applications.